SOCIO-CONSTRUCTIVISM-BASED CLASSROOM MANAGEMENT TO ENHANCE STUDENT-CENTERED LEARNING - Kiki Baehaqi Saepul Millah (Journal of English Education Program (JEEP), 2018)
This study is concerned with the teacher’s ways in implementing socio-constructivism-based classroom management and the students’ perceptions about the implementation of socio-constructivism that was applied by the teacher. Socio-constructivism is learning approach where the students construct their own knowledge and mental models as a result of their own experience and thinking by means of interacting with their environment (Gagon et al., 2006) as cited in Kaya and Donmez (2010). This study used a case study and applied qualitative approach involving one English teacher and three students including the students from low, middle, and high achievement. Observation and semi-structured interview were used to collect the data from the participants. The findings showed that the teacher implemented socio-constructivism-based classroom management in some ways. First, the teacher encouraged the students to find out the information about theme of teaching material. The second way is creating the product that was some text based on the theme given. The third ways is processing that the students worked in groups. The next way is sharing and retrieving. In this way the students share the information in their groups. The last way is evaluating which in the teacher asked the students to make the summary from each group presentations and gave correction to the students’ performance in presenting the PowerPoint. Moreover, data from interview showed that the students were enjoy, enabled to work cooperatively in groups, help each other to find out the information, and the different perceptions of the student from low achievement that he found the difficulties in translating the language and lack of vocabulary.